Українська археологія: стан і перспективи (суб'єктивне враження про об'єктивний стан) - Залізняк, Л.Л. (Археологія і давня історія України, 2019)
Значний стаж роботи у великому науковому колективі провідної археологічної установи країни — Інституті археології НАНУ (50 років) надав сміливості автору цих рядків висловити свої суб’єктивні враження про стан і можливі перспективи української археології. У статті автор торкається складних проблем боротьби зі злочинним промислом «чорних копачів» в Україні, чим вже багато років переймається шановний ювіляр Юрій Вікторович Болтрик. Ukraine is one of the richest on archaeological sights countries of Eastern Europe. However this riches strike a discordant note with the traditionally small amount of the Ukrainian archaeologists. The lack of «white» academic and university archaeologists is compensated in Ukraine by the increase of quantity of «black archaeologists » that engage in the plunder of archaeological inheritance of country. Strategy of fight against illegal trade of archaeological artefacts it follows fundamentally to reform in Ukraine, limiting to him the hard scopes of law. Above «black archaeologists» it follows to set hard control of public organs with bringing in of professional archaeologists.